KONSEP PEMIKIRAN EKONOMI IMAM ABU HANIFAH - Rizki, Raden Hasnan Muhamad (Tijarah: Jurnal Ekonomi Syariah, 2023)
This research examines the important role of Islamic law in the social and spiritual life of Muslims, emphasizing that understanding Islam is incomplete without understanding its laws. Islamic law, which is called the most special science by Joseph Schacht, is necessary to understand the principles and practices of economics in Islam. Imam Abu Hanifah, through his work Al-Makharif fi Al-Fiqh, has integrated Islamic economics with fiqh, showing that Islamic economics is an inseparable part of broader Islamic law. The loss of historic Islamic economic traditions, described by Joseph Schumpeter as the “Great Gap,” highlights the importance of restoring and modernizing Islamic economics to address contemporary economic challenges. The research methodology used is qualitative with descriptive analysis, focusing on the contribution and views of Imam Abu Hanifah towards Islamic economics. The research results show that the economic principles and practices promoted by Imam Abu Hanifah are still relevant and can provide solutions to modern economic problems, by prioritizing ethical and moral principles in economics. ABSTRAKPenelitian ini mengkaji peran penting hukum Islam dalam kehidupan sosial dan spiritual umat Islam, menekankan bahwa pemahaman Islam tidak lengkap tanpa memahami hukumnya. Hukum Islam, yang disebut sebagai ilmu paling istimewa oleh Joseph Schacht, diperlukan untuk memahami prinsip dan praktik ekonomi dalam Islam. Imam Abu Hanifah, melalui karyanya Al-Makharif fi Al-Fiqh, telah mengintegrasikan ekonomi Islam dengan fiqh, menunjukkan bahwa ekonomi Islam merupakan bagian tak terpisahkan dari hukum Islam yang lebih luas. Kehilangan tradisi ekonomi Islam yang bersejarah, yang dijelaskan oleh Joseph Schumpeter sebagai "Great Gap," menyoroti pentingnya memulihkan dan memodernisasi ekonomi Islam untuk mengatasi tantangan ekonomi kontemporer. Metodologi penelitian yang digunakan adalah kualitatif dengan analisis deskriptif, berfokus pada kontribusi dan pandangan Imam Abu Hanifah terhadap ekonomi Islam. Hasil penelitian menunjukkan bahwa prinsip dan praktik ekonomi yang diusung Imam Abu Hanifah masih relevan dan dapat memberikan solusi atas masalah ekonomi modern, dengan mengedepankan prinsip-prinsip etis dan moral dalam ekonomi.